120:oral Developing and implementing a framework for priority setting in health and social care in Scotland. (28th April 2022) - Collins, Marissa; Baker, Rachel; Mazzei, Micaela; Donaldson, Cam; Morton, Alec; Frith, Lucy; Syrett, Keith; Leak, Paul
Abstract : There is a move, internationally, towards greater integration of health and social care. In principle, integration reduces budgetary boundaries which can facilitate sharing of resources across health and social care. Part of the agenda is for local delivery organisations to alter the balance of care from acute to community environments. To facilitate this shift, against a background of increasing austerity, there is a need for robust processes for making difficult resource allocation decisions which meet the standards of disciplines such as economics, ethics, law and decision science. In 2014, the Scottish Government established 31 Health and Social Care Partnerships (HSCPs) acting as single commissioners to deliver this agenda. The aim was to develop and implement an enhanced, multi-disciplinary framework for priority setting, for use by four HSCPs, and assess its impact on processes, decision-making and resource allocation. Methods: To develop the framework, a literature review was conducted. The findings form the review were combined with input from key stakeholders including, academics, local and national-level stakeholders. During implementation of the framework, Participatory Action Research was undertaken to explore how the framework functioned within HSCPs, to document how participants engaged with the framework and to consider how the framework could be adapted to an integrated institutional setting. Interviews were conducted before and after working with the framework. Results: The framework is underpinned by principles from economics (opportunity cost), decision-analysis (good decisions), ethics (justice) and law (fair procedures). Three sites worked through the process and made recommendations. Proposed recommendations include disinvestment and reallocations within budget areas. Despite challenges, stakeholders' views were that such a framework is required to move from resource allocations being based on historical budgets and service provision and encourages transparent decision making involving wider stakeholders. Increased pressure on resources has made such frameworks even more critical for decision making.